Design of Irrigation System Based on Arduino Uno Using Soil Moisture Sensor - Ariwibowo, Muhamad Riyad (Electrical Engineering Departement, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Water needs are very necessary for the agricultural sector in caring for plants properly. However, in the management process, farmers have a watering time that is not tools used to help farmers’ performance. With automatic irrigation system technology, farmers can take advantage of solutions to make it easier to care for plants. The automatic irrigation system utilizes and Arduino Uno based soil moisture sensor as a soil moisture detector. Soil moisture sensors are tested for soil moisture in dry, slightly moist, wet and mossy soil conditions. The test results show that the sensor can read the condition of soil moisture < 60%, then the waterpump does not move and does not water automatically, otherwise if the soil moisture > 60% will work automatically with the average soil moisture produced after watering by 61% and obtain a neutral pH.